STRUCTURAL REMODELING OF THE EPILEPTIC BRAIN: AN ANATOMICAL AND HISTOPATHOLOGICAL REVIEW - Oluwaseyi Emmanuel Kolawole; Oluseyi Sunday Fabiyi; Olugbenga Olawole Olayinka; Caroline Ifeoluwa Olakanmi; Kehinde Lawal; Onyema Kelechi Roselyn (World Journal of Biology Pharmacy and Health Sciences, 2026)
Epilepsy is increasingly recognized not merely as a functional electrical disorder but as a condition associated with progressive and, in many cases, region-specific structural reorganization of the brain. Neuroimaging and histopathological studies over the past two decades have demonstrated that recurrent seizures are accompanied by hippocampal sclerosis, mossy fiber sprouting, granule cell dispersion, cortical thinning, white matter tract disruption, and, in some models, alterations extending to extra-limbic and even extra-cranial structures. These structural alterations are not static end-points but evolve dynamically with disease duration, seizure frequency, and etiology, and they carry important implications for diagnosis, prognosis, and surgical planning. This review synthesizes current evidence on structural brain changes in epilepsy, drawing on human neuroimaging and histopathology literature as well as preclinical rodent studies, including several recent Nigerian experimental studies using lithium chloride-pilocarpine and kainic acid models that have examined hippocampal, prefrontal cortical, and limbic architecture following induced seizures and after treatment with plant-derived neuroprotective agents. We discuss the cellular and molecular underpinnings of hippocampal sclerosis, cortical and subcortical atrophy, white matter and network level changes, and the emerging use of structural biomarkers, while highlighting therapeutic strategies, including antiepileptic drugs, ketogenic diet, and Phyto therapeutic agents, that may attenuate or reverse these structural sequelae.